AB0210 Effects of Endothelin-1 on M2 Macrophage Polarization in Cultured Human Macrophages. (10th June 2014) - Soldano, S.; Montagna, P.; Brizzolara, R.; Sulli, A.; Paolino, S.; Cutolo, M.
Abstract : Background: Macrophage lineage may undergo two different polarization states: classically activated (M1) and alternatively activated (M2) macrophages: both macrophage populations represent the extremes of a continuum of functional states (1, 2). M1 seem implicated in T helper type 1 (Th1/M1) responses with the production of proinflammatory cytokines (IL6, IL1β, TNFα), whereas M2 seem involved in Th2 responses (Th2/M2). Moreover, M2 macrophages are characterized by high expressions of mannose receptor (CD206) and scavenger receptors (i.e. CD204) that promote tissue remodelling and the wound-healing process, leading to the production of profibrotic mediators (i.e. TGFβ) (2). Endothelin-1 (ET1) plays a role in fibrotic process, and high plasma/tissue levels have been observed in systemic sclerosis (SSc) patients (3, 4). Objectives: To investigate possible effects of ET1 in promoting the M2 macrophage phenotype polarization in cultured human macrophages. Methods: Human monocyte (THP1) cells were plated in Flex Perm chamber slides (1x10 6 cells/ml), activated to macrophages with phorbol myristate acetate (PMA, 25ng/ml), and treated for 48 hrs with ET1 (100nM) and interferon-γ (IFNγ, 500U/ml) in RPMI at 5% of fetal bovine serum. As known, IFNγ was used as a potent inducer of M1 macrophage phenotype (1). PMA-treated cells were used as controls. The expression of CD68, as general marker of macrophage phenotype, as well as the expression of CD206 and CD204 (scavenger receptor A), as markers of M2 macrophage phenotype, were investigated by immunocytochemistry (ICC). CD204 and CD206 protein synthesis was indicated as % of positive area. Results: At ICC analysis ET1 was found able to induce a clear expression of CD206 in about 60% of cells compared to controls (negative) (% of positive area: 1.53±0.5 vs. 0.34±0.08) and it increased the expression of CD204 compared to controls (% of positive area: 2.03±0.3 vs. 1.36±0.2). As expected, IFNγ did not induce any expression of CD206, although a slight increase in the expression of CD204 was observed compared to untreated controls (% of positive area: 1.7±0.15 vs. 1.36±0.2). ICC showed the ability of cultured cells to co-express CD68, confirming in any case their activation into macrophages. Conclusions: Present preliminary observations show that ET1 may stimulate macrophage polarization to the alternatively activated M2 macrophage phenotype (expression of CD206 and CD204), which has been already identified in several fibrotic diseases, including SSc (5). Of note, human skin fibroblasts stimulated with paracrine factors secreted by M2 macrophages display an increased proliferation rate (6).The M2 polarization induced by ET-1 in cultured macrophages might represent one of the immunomodulatory mechanisms involved in the progressive tissue fibrosis. References: Wynn TA et al. Nature 2013;496:445-55. Mantovani A et al. J Pathol 2013;229:176-85. Wynn TA. Nat Rev Immunol 2004;4:583-94. Sulli A et al. J Rheumatol 2009;36:1235-9. Higashi-Kuwata N et al. Arthrit Res Ther 2010;12:R128. Leask A. Pharmacol Res. 2011;63:502-3. Ploeger DT, Cell Commun Signal. 2013;11:29-34. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3605